Gendered Norms and HRM Practices at Workplace: Evidence from Public Banking Sector in Sri Lanka. Issue 2 (August 2019) - Kodagoda, Thilakshi
This article seeks to understand under-representation of women in the top managerial positions in Sri Lanka's public banking sector and how HRM practices at the workplace impact their careers. The narratives of women bank managers show that they possess skills, confidence and a desire to climb up the career ladder. However, women's ambitions for managerial positions and promotion to decision-making levels are implicitly limited by the state bureaucracy. Organizations need to establish and maintain better human resource practices and organizational culture for gender equality as well as organizational effectiveness. The article offers policy implications and avenues for future research. It is based on a study of 15 women managers working in the public banking sector. In-depth, semi-structured interviews with these key respondents formed the core research technique.